The relationship between personality traits and safety behavior among manufacturing workers - Nurris Sabrina, Muhamad Saferi (2025)
Ensuring workplace safety is critical concern in the manufacturing sector, where the risk of accidents and injuries is naturally high. This study investigates the relationship between personality traits and safety behavior among manufacturing workers at three factories in Kuala Terengganu, Terengganu, with a total of 108 workers. This study utilized the Big Five Inventory (BFI), to assess the personality traits of manufacturing workers. This method allowed for the identification of key personality traits such as openness, conscientiousness, extraversion, agreeableness, and neuroticism, and examines their impact on safety behavior. This study reveals that agreeableness (m = 3.14) and conscientiousness (m = 3.05) are the most prevalent traits among workers, contributing positively to a collaborative and safety-conscious work environment. The evaluation of safety behavior indicates a moderate level of compliance with safety protocols (m = 3.51), with areas for improvement in post-accident responses (m = 2.68) and safety training participation (m = 3.24). Spearman’s correlation analysis shows a slight positive association between openness and safety behavior (r = 0.040, p = 0.684) and a somewhat greater positive connection for conscientiousness (r = 0.135, p = 0.164). Extraversion shows no connection (r = 0.000, p = 0.000), while agreeableness (r = -0.145, p = 0.133) and neuroticism (r = -0.097, p = 0.317) show slight negative connections with safety behavior. These findings highlight the importance of tailored safety interventions that consider individual personality traits to enhance safety outcomes. The study underscores the need for management to foster a proactive safety culture and continuous safety education to improve overall safety performance in the manufacturing sector.